Zeros of Analytic Continued q-Euler Polynomials and q-Euler Zeta Function. (21st July 2014) - Ryoo, C. S.
Abstract : We study that the q -Euler numbers E n, q and q -Euler polynomials E n, q ( x ) are analytic continued to E q ( s ) and E q ( s, w ) . We investigate the new concept of dynamics of the zeros of analytic continued polynomials. Finally, we observe an interesting phenomenon of ''scattering'' of the zeros of E q ( s, w ) .